Os pais e a possibilidade da morte do filho prematuro de risco - Guianze, Marluce de Freitas Martins (2000)
This is a qualitative study showing how parents deal with the possibility of death when their premature child is hospitalized. Twenty families with children in the neonatal ICU of the Instituto Fernandes Figueira were interviewed The purpose was to verify how parents perceive their babies' hospitalization and the risk of death. The contents of these interviews were analyzed according to Martins and Bicudo' s method. The theoretical bases for this project were the concepts of mourning, anticipation of mourning and attachment. The results showed that fear of death is present in all interviews and that it interferes in the development of the attachment process. High quality assistance given to the parents by the medical staff seems to favor the reestablishment of the emotional bond. We conclude that when parents see their children in hospital they realize that they are fragile, unfinished human beings whose lives are at risk. Thus, they tend to show the characteristic behavior of mourning which affects the attachment process. The time of mourning for the beautiful and healthy imaginary baby must come to an end before parents can reestablish their attachment to the small premature. Only then can the baby develop normally. The medical staff contribute to the development of the parent-child bond by giving parents information and by encouraging them to participate in the treatment process.